Analysis of the Miracles of the Qur'an in the Development of the Ulumul Qur'an: Mukjizat Al-Qur'an Dalam Perkembangan Ulumul Qur'an - Susanta, Edris Susanta; Khotimah, Husnul (Institut Agama Islam Persis Bandung, 2025)
[Analysis of the Miracles of the Qur'an in the Development of the Ulumul Qur'an) This research aims to examine the Miracles of the Qur'an in the development of the Ulumul Qur'an, to reveal hidden signals regarding the Miracles in the development of the Ulumul Qur'an from various aspects, such as language, content, interpretation, and its relationship with science. Muslims must be active in studying the Ulumul Qur'an because when we understand it, our hearts and souls will be inspired by the privileges of His word through knowledge of the Qur'an. This research uses qualitative methods with a historical and analytical approach to library research. This means that the data source for this research comes from written works because, in the data collection process, the researcher did not carry out direct field research, and only took references in books, documents, and journals related to the main focus of the discussion. namely the analysis of the miracles of the Koran in the development of the Ulumul Koran. The data used are various literature sources related to the Ulumul Koran. The data obtained was then analyzed using descriptive-analytic techniques. The results of this research show that the Ulumul Koran has dynamic and diverse developments, by the conditions of the times and the needs of the people. The Ulumul Koran also has various branches of knowledge that are interrelated and complementary, such as the science of i'jaz, the science of munasabah, the science of asbabun nuzul, the science of nasikh wa mansukh, the science of muhkam wa mutasyabih, the science of aam wa khoos, and the science of scientific signs. Ulumul quran is very important to learn because it can help us understand and interpret the Koran correctly, as well as admire the wonders and truth of the word of Allah SWT. The arguments that show the miracle of the Al-Quran include the beauty and uniqueness of the language and literary style of the Al-Quran, news that cannot possibly be reached by the human mind, there is no conflict between the concepts of the Al-Quran and the reality of the findings and scientific inquiry, and the spread of the Koran throughout the world.